Epigenetic regulation of subgenome dominance following whole genome triplication in Brassica rapa. Issue 1 (12th February 2016) - Cheng, Feng; Sun, Chao; Wu, Jian; Schnable, James; Woodhouse, Margaret R.; Liang, Jianli; Cai, Chengcheng; Freeling, Michael; Wang, Xiaowu
Summary: Subgenome dominance is an important phenomenon observed in allopolyploids after whole genome duplication, in which one subgenome retains more genes as well as contributes more to the higher expressing gene copy of paralogous genes. To dissect the mechanism of subgenome dominance, we systematically investigated the relationships of gene expression, transposable element (TE) distribution and small RNA targeting, relating to the multicopy paralogous genes generated from whole genome triplication in Brassica rapa . The subgenome dominance was found to be regulated by a relatively stable factor established previously, then inherited by and shared among B. rapa varieties. In addition, we found a biased distribution of TEs between flanking regions of paralogous genes. Furthermore, the 24‐nt small RNAs target TEs and are negatively correlated to the dominant expression of individual paralogous gene pairs. The biased distribution of TEs among subgenomes and the targeting of 24‐nt small RNAs together produce the dominant expression phenomenon at a subgenome scale. Based on these findings, we propose a bucket hypothesis to illustrate subgenome dominance and hybrid vigor. Our findings and hypothesis are valuable for the evolutionary study of polyploids, and may shed light on studies of hybrid vigor, which is common to most species.